Quality Improvement Initiative Increasing Early Discharges From an Acute Care Cardiology Unit for Cardiac Surgery and Cardiology Patients–Associated With Reduced Hospital Length of Stay. Issue 4 (1st July 2022) - Colyer, Jessica; Ring, Lisa; Gallagher, Sarah; Mullenholz, Mary; Robison, Jan; Rigney-Radford, Kathleen; Harahsheh, Ashraf S.
Abstract : Introduction: Discharging patients from the acute care setting is complex and requires orchestration of many clinical and technical processes. Focusing on timely discharges improves throughput by off-loading ICUs and coordinating safe outpatient transitions. Our data review demonstrated most discharges occurred later in the day. We sought to improve our discharge times for cardiology and cardiovascular surgery (CVS) patients in our 26-bed inpatient acute care cardiology unit (ACCU). We aimed to increase the number of discharges between 6 am and 12 pm for cardiology and CVS patients on ACCU from 5 to 10 patients per month over 6 months and sustain. Methods: We performed a simplified Failure Mode Effect Analysis on the discharge process and identified improvement opportunities. Our key drivers centered around education, documentation, and planning. Our interventions included: staff education, communication of discharge expectations, daily quality board rounds, hospital-wide collaboration emphasizing conditional discharges, and hospital information technology (IT) improvements. We utilized statistical process control charts to analyze the data. Results: Discharges between 6 am, and 12 pm increased from a baseline of 5 (8%) to 12 (18%) patients per month with a centerline shift. Our process measures demonstrated appropriate conditional discharge usage linked to earlier discharges. Upgrades to our EMR, documentation further increased our timely discharges. Our efforts resulted in a 22% reduction in hospital length of stay from 11.2 to 8.7 days without increased readmission rates suggesting that improved efficiency did not impact care quality. Conclusion: We successfully show how multidisciplinary collaboration and systems-based improvement can increase the number of safe, early discharges.